MENGOPTIMALKAN POTENSI HEMISTER (OTAK KANAN) DALAM PROSES PEMBELAJARAN - Afrizal Afrizal (AL-ISHLAH: Jurnal Pendidikan, 2017)
The brain is the greatest gift of god for human. This brain consists of 2 parts. They are the right brain and left brain. Each part has a specific function. The right brain has a 90% memory capacity and left brain is only 10-12%. Recent research results was in the US said that  the role of logic in making people become successful is only 4-6%, while 94-96% is determined by  the right brain that  associated alot with innovation, creativity, instinct, intuition, creativity, honesty, tenacity, responsibility, and others. In the learning process the balance of the two   brains are  very important to think optimally. Some of the efforts to optimize the right brain potential are  Intelligent Movement, Game / Puzzle, Music, Social Communication and Hobby.